2011
DOI: 10.1309/ajcp2f2doxotxhza
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of CD1d Expression in a Large Cohort of Patients With B-Cell Chronic Lymphoproliferative Disorders

Abstract: Immunophenotyping is indispensable in the differential diagnosis of B-cell chronic lymphoproliferative disorders (B-CLPDs). However, B-CLPDs often show overlapping immunophenotypic profiles and may be diagnostically challenging. CD1d is an HLA class I-like molecule that presents glycolipids to invariant natural killer T cells. Normal mature B cells constitutively express CD1d, but with the exception of some conflicting data, its expression in B-CLPDs is unknown. We demonstrate that in 222 B-CLPD cases, CD1d ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
(51 reference statements)
5
24
0
1
Order By: Relevance
“…37 This study confirms that CLL cells express surface CD1d, but at a level modestly lower than on normal B cells. 38 Despite this, we found that α-GalCer-treated CLL cells were able to elicit iNKT cell proliferation, confirming a previous finding.…”
Section: Discussionsupporting
confidence: 79%
“…37 This study confirms that CLL cells express surface CD1d, but at a level modestly lower than on normal B cells. 38 Despite this, we found that α-GalCer-treated CLL cells were able to elicit iNKT cell proliferation, confirming a previous finding.…”
Section: Discussionsupporting
confidence: 79%
“…The present study showed lower CD1d expression in CLL patients compared with healthy controls. Consistent with our results Kotsianidis et al [13] reported higher surface expression of CD1d in healthy controls than in CLL patients. A recent study reported that measuring CD1d by flow cytometer and quantitative reverse transcriptase PCR showed lower CD1d molecule and CD1d mRNA expression in B-cells of CLL patients than of healthy controls [14] .…”
Section: Discussionsupporting
confidence: 93%
“…Previous few studies demonstrated an association between CD1d expression and the adverse immunophenotypic feature, namely CD38 expression in CLL patients [13,24] . By contrast, another research group detected no significant differences between Zap-70 positive and negative, CD38 positive and negative CLL sub groups [25] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations